Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/molecules27030820
|View full text |Cite
|
Sign up to set email alerts
|

A Green Extraction Method to Achieve the Highest Yield of Limonin and Hesperidin from Lime Peel Powder (Citrus aurantifolia)

Abstract: Green extraction is aimed at reducing energy consumption by using renewable plant sources and environmentally friendly bio-solvents. Lime (Citrus aurantifolia) is a rich source of flavonoids (e.g., hesperidin) and limonoids (e.g., limonin). Manufacturing of lime products (e.g., lime juice) yields a considerable amount of lime peel as food waste that should be comprehensively exploited. The aim of this study was to develop a green and simple extraction method to acquire the highest yield of both limonin and hes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
(52 reference statements)
1
16
0
Order By: Relevance
“…The IC 50 level estimated from the statistic is 503.004 μg/mL (at 72 h, 95% CI). Upon considering concentrations of compounds only, the concentrations of hesperidin and limonin in lime peel extract at IC 50 levels are 0.2868 μg/mL and 0.0139 μg/mL, respectively (measured by the method following our previous study [ 18 ]). It is 580 and 13,628 times less than the IC 50 of pure compounds of hesperidin and limonin, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The IC 50 level estimated from the statistic is 503.004 μg/mL (at 72 h, 95% CI). Upon considering concentrations of compounds only, the concentrations of hesperidin and limonin in lime peel extract at IC 50 levels are 0.2868 μg/mL and 0.0139 μg/mL, respectively (measured by the method following our previous study [ 18 ]). It is 580 and 13,628 times less than the IC 50 of pure compounds of hesperidin and limonin, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Lime peel powder was extracted following the optimum condition method from a previous study [ 18 ]. Lime peel powder was extracted with 80% ethanol in water at pH 7 in a 50 °C shaking water bath (Memmert GmBH Co., Büchenbach, KG, Germany) at a shaking speed level of 3.5 for 100 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was previously shown that the concentration of ethanol (as the extraction solvent), pH of the solvent, and extraction temperature greatly impacted the extraction yields of flavonoids and limonoids, such as hesperidin and limonin, respectively, in lime ( C. aurantifolia ) peel [ 4 ]. The extraction yield of hesperidin was increased when the ethanol concentration (as percentage of ethanol in water) was increased in aqueous ethanolic solvents ranging from 60–80% [ 4 ]. However, the extraction yield declined in absolute ethanol [ 4 ].…”
Section: Introductionmentioning
confidence: 99%